North Korean human rights the road ahead - Cha, Victor D. 1961-; DuMond, Marie (CSIS report, 2015)
To commemorate the one-year anniversary of the report by United Nations Commission of Inquiry on human rights in the Democratic People's Republic of Korea, CSIS held an unprecedented gathering of policymakers, opinion leaders, and stakeholders on the topic of North Korean human rights. The gathering aimed to carry forward the momentum created by the United Nations Commission of Inquiry report and subsequent UN actions. The conference was organized by the Center for Strategic and International Studies, the Committee for Human Rights in North Korea (HRNK), the George W. Bush Institute, and the Yonsei Center for Human Liberty. This report summarizes those proceedings